2020
DOI: 10.1007/s40415-020-00594-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic diversity and population structure of Carica papaya L. revealed through nuclear microsatellites

Abstract: It is crucial to analyze the population structure and genetic diversity of the samples to be studied before a breeding program can be launched. Thirty-one genotypes of papaya germplasm from Spain, Brazil, Ecuador, China, Taiwan, India, and several locations in Bangladesh were genotyped using ten polymorphic simple sequence repeat markers to investigate their molecular diversity as well as their genetic relatedness. The highest numbers of alleles, gene diversity and polymorphic information content were seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Results of AMOVA indicated that 17.35% of the total genetic diversity was due to differences within populations, while 45.80% of the overall genetic diversity was a result of differences among the population. These relatively low values of variation may be justi ed by the reproductive system of the species (Luo et al 2007;Hasibuzzaman et al 2020) dispersion of the species among farmers (Ov et al 2011), and evolutionary changes within the species. Haplotype diversity re ects the degree of difference among the haplotypes in each population.…”
Section: Discussionmentioning
confidence: 99%
“…Results of AMOVA indicated that 17.35% of the total genetic diversity was due to differences within populations, while 45.80% of the overall genetic diversity was a result of differences among the population. These relatively low values of variation may be justi ed by the reproductive system of the species (Luo et al 2007;Hasibuzzaman et al 2020) dispersion of the species among farmers (Ov et al 2011), and evolutionary changes within the species. Haplotype diversity re ects the degree of difference among the haplotypes in each population.…”
Section: Discussionmentioning
confidence: 99%
“…Papaya is diploid (2 n = 18) (Chávez‐Pesqueira & Núñez‐Farfán, 2017; Hasibuzzaman et al., 2020) with three flower sex types, that is, males, females, and hermaphrodites, controlled by a single locus with at least three alleles: M1, a dominant allele for male plants; M2, a different dominant allele for hermaphrodite plants; and m, a recessive allele for female plants. All combinations of dominant alleles, that is, MM, MMh, and Mh Mh (where M represents the male and Mh represents the hermaphrodite alleles) are lethal to the zygote (Lee et al., 2018).…”
Section: Markers In Selected Species Of Fruit Cropmentioning
confidence: 99%